Effectiveness of E-Supplement Mobile Android Application toward Science Literacy Skills on Minimum Competency Assessment Oriented in Respiratory System of Junior High School Students - Alfan, Dheny Choirul; Saptono, Sigit; Lisdiana, Lisdiana (Universitas Negeri Semarang)
Learning on 21st century is supported by sophisticated technology, where the demands on situations and conditions require people to be able in adjusting all experiences possessed to solve problems scientifically in everyday life. Students' analytical skills and scientific thinking in daily life become one of the important aspects that support the achievement of educational goals. This research aims to analyze the science literacy skills of students grade 8 at State Junior High School 2 Tulung, Klaten while learning Respiration System applied by E-Supplement Mobile Android on Minimum Competency Assessment-Oriented. This study used method of Research and Development for 102 students of respondents from 4 classes. The research is designed by ADDIE. The results of the pot-test scores were higher than the pre-test scores with an average of 82.74% with classical completeness of 81.37% and the N-Gain test results of 56% in the high category. In addition, the application of the e-supplement mobile android application effectively improves students’ scientific literacy skills in terms of knowledge and competence.